PENGARUH TERAPI PIJAT REFLEKSI KAKI TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI - Cicielia Ernawati Rahayu; Fani Hanifah (NHM PRESS, 2023)
Hypertension is a state of systolic blood pressure 140 mmHg and diastolic 90 mmHg. Hypertension is known as a silent killer because it is the most common and has no known cause. Based on the 2018 RISKESDAS in Indonesia, the prevalence of hypertension in DKI Jakarta is the fifth highest (10.17%). Hypertension is caused by several factors such as age, gender and genetics. Non-pharmacological management of hypertensive patients can be done with massage, one of which is foot reflexology therapy. From literature review , it is hoped that researchers will get the effect of foot reflexology therapy on reducing blood pressure in hypertensive patients. Research This study uses a literature review that uses data sources obtained from searching the google scholar database with journal topics in Indonesian and English in the 2016-2021 range. Literature review from 7 journals, obtained significant results in reducing blood pressure after being given an intervention in the study (Marisna, Desi et al. 2017) with interventions carried out 3 times a week with a duration of 30 minutes. Foot reflexology therapy is effective in reducing blood pressure in hypertensive patients with the intervention given 3 times a week with a duration of 30 minutes.